A method of manufacturing an electrode foil, an electrode foil, and a curable gel electrolyte
Patent Information
- Application Number
- CN202611402117.1
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2026-09-10
- Publication Date
- 2026-11-03
AI Technical Summary
In the prior art, problems such as low capacity utilization of electrode foil due to uneven filling of conductive polymer, poor high-temperature stability due to interfacial thermal mismatch, and high ESR due to large interfacial contact resistance limit the performance and reliability of multilayer aluminum electrolytic capacitors.
An interpenetrating network structure was constructed within the micropores of the electrode foil. A gradient concentration impregnation strategy and in-situ cured gel electrolyte were employed, combined with a resistance gradient conductive structure, to form synergistic electron transport channels and ion transport channels, thereby optimizing the filling of the conductive polymer and the interfacial resistance.
It significantly improves the capacitance extraction rate of the electrode foil, reduces the equivalent series resistance, enhances high-temperature stability and long-term reliability, and improves the high-frequency response performance and manufacturing precision of the capacitor.
Smart Images

Figure CN123033897A_ABST
Abstract
Description
Technical Field
[0001] This invention relates to the field of capacitor manufacturing technology, and specifically to an electrode foil for multilayer aluminum electrolytic capacitors and its preparation method. Background Technology
[0002] Multilayer aluminum electrolytic capacitors are widely used in consumer electronics, industrial control, and new energy vehicles due to their high volumetric capacitance and excellent frequency characteristics. One of their core components is the anode electrode foil, which is typically made of high-purity aluminum foil that has undergone electrochemical etching and anodizing, resulting in a microporous structure with a high aspect ratio and an alumina dielectric layer on its surface. To reduce the equivalent series resistance (ESR) and improve performance, the industry tends to use conductive polymers (such as poly(3,4-ethylenedioxythiophene), i.e., PEDOT) as a solid electrolyte to fill the micropores.
[0003] However, existing conductive polymer filling processes face significant challenges. In traditional multi-impregnation in-situ polymerization, due to the extremely high aspect ratio of the microporous structure, a natural concentration gradient exists in the diffusion of the reactant solution within the pores. This often leads to preferential rapid growth and over-accumulation of the polymer at the pore openings, hindering the penetration of subsequent reactants into the depths of the micropores, forming a so-called "sealing effect." This uneven filling not only results in a low effective filling rate of the polymer, typically only 55-65%, but more importantly, it prevents the alumina dielectric layer deep within the micropores from effectively contacting the electrolyte, wasting a large amount of potential energy storage surface area and severely limiting the actual capacitance extraction rate of the capacitor.
[0004] Furthermore, the long-term reliability of the device, especially its high-temperature stability, is another key bottleneck. The conductive polymer, as an organic material, has a significantly different coefficient of thermal expansion compared to the inorganic alumina dielectric layer. During operation or storage over a wide temperature range (e.g., -55°C to 125°C), repeated thermal expansion and contraction create stress at the interface, easily inducing the generation and propagation of microcracks. These microscopic defects disrupt charge transport paths, leading to irreversible ESR degradation, significantly shortening the device's lifespan, and limiting its application in high-reliability fields such as aerospace and automotive electronics.
[0005] Finally, the efficiency of charge conduction from the inside of the electrode foil to the external circuit also directly affects device performance. Conductive polymers are essentially semiconductor materials, and their conductivity differs by several orders of magnitude from that of commonly used metal leads (such as copper or aluminum) in external circuits. This significant abrupt change in conductivity creates a high Schottky barrier at the interface between the two, i.e., a large interfacial contact resistance. This resistance is a crucial component of the capacitor's total ESR, increasing energy loss and limiting the device's charge / discharge rate and high-frequency response.
[0006] In summary, there is an urgent need for a novel electrode foil fabrication method to systematically solve the interconnected technical challenges, such as low capacity utilization due to uneven filling of conductive polymers, poor high-temperature stability due to interfacial thermal mismatch, and high ESR due to high interfacial contact resistance. Summary of the Invention
[0007] To address the problems of low capacity extraction rate, high equivalent series resistance, and poor long-term reliability of electrode foils caused by uneven filling of conductive polymers, insufficient high-temperature stability, and high interfacial contact resistance in existing technologies, this invention provides a method for preparing electrode foils, the electrode foils themselves, and a curable gel electrolyte.
[0008] According to one aspect of the present invention, a method for preparing an electrode foil for a multilayer aluminum electrolytic capacitor is provided, the electrode foil comprising an aluminum foil having micropores, the method comprising: pretreating the inner wall of the micropores to improve its wettability to subsequent reaction solutions; and forming an interpenetrating network structure comprising electron transport channels and ion transport channels within the micropores. By constructing synergistic dual transport pathways within the micropores, efficient exchange and transport of charge deep within the micropores can be ensured, thereby fundamentally improving the electrochemical performance of the electrode foil.
[0009] Furthermore, the step of forming the interpenetrating network structure includes: performing multiple cycles of in-situ polymerization using a gradient concentration impregnation strategy to generate a conductive polymer network serving as the electron transport channel within the micropores, wherein the initial cycle uses a higher concentration of monomer solution and oxidant solution, and the subsequent cycle uses a lower concentration of monomer solution and oxidant solution; and impregnating an aluminum foil with the conductive polymer network into a curable gel electrolyte containing nanoscale inorganic fillers, and curing the gel electrolyte in situ to form a gel electrolyte serving as the ion transport channel in the gaps between the conductive polymer network. This gradient concentration strategy effectively overcomes the "sealing effect," achieving uniform filling of the conductive polymer from the inside out, while the in-situ cured gel electrolyte constructs an efficient ion transport pathway.
[0010] Optionally, during the multiple cycles of in-situ polymerization, ultrasonic-assisted treatment is applied, and sodium polystyrene sulfonate is added to the oxidant solution as a dopant. The cavitation effect of ultrasound helps to eliminate bubbles in the micropores and enhances solution permeability; while the introduction of the dopant can significantly improve the intrinsic conductivity of the conductive polymer network and further reduce the resistance of the electron transport channels.
[0011] In one embodiment, the pretreatment includes plasma treatment of the aluminum foil or chemical treatment with a silane coupling agent solution; the method further includes coating the untreated areas of the aluminum foil with a double-layer shielding structure comprising a chemically resistant inner layer and a hydrophobic outer layer; and the method further includes sequentially depositing a conductive transition layer, an alloy transition layer, and a highly conductive outer layer on one side surface of the aluminum foil substrate to form a resistance gradient conductive structure. These preferred solutions optimize the overall performance of the electrode foil from multiple dimensions, such as improving interfacial bonding, increasing manufacturing precision, and reducing external contact resistance.
[0012] According to another aspect of the present invention, an electrode foil for a multilayer aluminum electrolytic capacitor is provided, comprising an aluminum foil having micropores, characterized in that an interpenetrating network structure is provided within the micropores, the interpenetrating network structure comprising: an electron transport channel made of a conductive polymer; and an ion transport channel made of a gel electrolyte filling the gaps in the electron transport channel.
[0013] Furthermore, the gel electrolyte contains nano-silica as an additive to enhance mechanical properties and thermal stability. The introduction of nanofillers can strengthen the mechanical strength of the gel network and effectively buffer thermal stress, thereby improving the structural stability and lifespan of the electrode foil under harsh temperature conditions.
[0014] Optionally, the electrode foil further includes a resistance gradient conductive structure disposed on one side surface of the aluminum foil substrate. The resistance gradient conductive structure comprises a conductive carbon layer, a silver-palladium alloy layer, and a highly conductive outer layer stacked sequentially. This structure effectively reduces the interfacial contact resistance between the internal semiconductor polymer and the external metal conductor through a smooth resistivity transition.
[0015] According to another aspect of the present invention, a curable gel electrolyte is provided, comprising: a crosslinkable monomer, a crosslinking agent, an initiator, a conductive salt, and nanoscale inorganic fillers for improving the mechanical properties and thermal stability after curing. This electrolyte composition, after in-situ curing, can form a solid electrolyte possessing both high ionic conductivity and excellent thermomechanical stability.
[0016] Preferably, the crosslinkable monomer is polyethylene glycol diacrylate, and the conductive salt is an organic carboxylic acid ammonium salt.
[0017] According to another aspect of the invention, a multilayer aluminum electrolytic capacitor is provided, comprising the electrode foil according to any of the preceding claims.
[0018] This invention fundamentally solves the bottleneck problem of poor charge transport deep within micropores by constructing an interpenetrating network structure consisting of a conductive polymer network (electron transport channels) and an in-situ solidified gel electrolyte (ion transport channels) within the micropores of the electrode foil. This allows for the efficient extraction of deep charges, thereby significantly improving the capacity extraction rate and actual output capacity of the electrode foil. Combined with a gradient concentration impregnation strategy, the effective filling rate of the micropores is significantly improved.
[0019] Meanwhile, by constructing a resistance gradient conductive structure consisting of a conductive carbon layer, an alloy transition layer, and a highly conductive outer layer on the back of the electrode foil, this invention achieves a smooth transition of conductivity from the internal semiconductor polymer to the external metal electrode, effectively reducing the interface contact resistance, thereby significantly reducing the overall equivalent series resistance of the device and improving its high-frequency response performance.
[0020] Furthermore, this invention employs an in-situ cured gel electrolyte containing nanoscale inorganic fillers, replacing traditional liquid electrolytes or pure polymer electrolytes. This gel electrolyte not only avoids the leakage and drying problems of liquid electrolytes, but its enhanced mechanical properties and thermal properties, which are more compatible with the inorganic dielectric layer, also effectively suppress interfacial microcracks caused by thermal stress, significantly improving the device's heat resistance, high-temperature operating stability, and long-term durability.
[0021] Finally, by coating the electrode lead-out area with a double-layer shielding structure that has both corrosion resistance and hydrophobicity, the chemical reaction area is precisely defined, effectively preventing contamination and short-circuit risks at the lead-out, thereby improving the precision, consistency, and yield of the final product in the manufacturing process. Attached Figure Description
[0022] Figure 1 This is a schematic flowchart of an electrode foil preparation method according to an embodiment of the present invention.
[0023] Figure 2 This is a schematic cross-sectional view of a portion of the electrode foil in the microporous region according to an embodiment of the present invention.
[0024] Figure 3 This is a schematic cross-sectional view of the overall layered structure of the electrode foil according to an embodiment of the present invention.
[0025] Figure 4 This is a schematic diagram of the overall structure of a multilayer aluminum electrolytic capacitor composed of electrode foil according to an embodiment of the present invention.
[0026] Explanation of reference numerals in the attached figures: S100 - Aluminum foil pretreatment, S110 - Microporous inner wall surface activation treatment, S200 - Polymerization region limitation, S300 - Multiple cycle in-situ polymerization, S400 - Gel electrolyte composite, S500 - Composite conductive layer preparation, S600 - Capacitor assembly and post-treatment. 10-Aluminum foil substrate, 20-Alumina dielectric layer, 30-PEDOT conductive network, 40-Gel electrolyte; 50-conductive carbon layer, 55-silver-palladium alloy layer, 60-conductive silver layer; 70 - Anode foil, 80 - Cathode foil, 90 - Insulating diaphragm, 100 - Positive lead, 110 - Negative lead, 120 - Package housing. Detailed Implementation
[0027] To make the objectives, technical solutions, and advantages of this invention clearer, the technical solutions of this invention will be described in detail below with reference to the accompanying drawings. It should be noted that, unless otherwise specified, the embodiments and features described in these embodiments can be combined with each other. The described embodiments are only some, not all, of the embodiments of this invention. All other embodiments obtained by those skilled in the art based on the embodiments of this invention without creative effort are within the scope of protection of this invention.
[0028] To facilitate understanding of the technical solution of this invention, some key terms involved in this application will first be explained. Among them, "interpenetrating network structure" refers to a composite structure formed within the micropores of an aluminum foil, where a three-dimensional continuous conductive polymer network serving as an electron transport channel and a gel electrolyte filling the gaps as an ion transport channel are spatially interwoven and permeated. This structure can work synergistically, providing an efficient dual pathway for charge storage and release.
[0029] The "electron transport channel" specifically refers to a three-dimensional network of conductive polymers formed within the micropores through in-situ polymerization and other methods. Its main function is to provide a low-resistance conduction path for electrons within the active region of the electrode foil. The "ion transport channel," on the other hand, refers to a network of in-situ solidified gel electrolytes filling the gaps in the electron transport channel network. Its main function is to provide a rapid and unobstructed migration path for electrolyte ions between the depths of the micropores and the surface of the dielectric layer.
[0030] The "gradient concentration impregnation strategy" employed in this invention refers to the strategic adjustment of reactant (such as monomers and oxidants) concentrations during multiple cycles of in-situ polymerization, rather than using a constant concentration of reactant solution. Typically, a higher concentration solution is used in the early stages of polymerization to leverage the strong osmotic pressure and driving force, enabling the reactants to rapidly penetrate deep into the microporous structure and form initial polymerization nuclei. In the later stages of polymerization, a lower concentration solution is used to slow the polymerization rate at the micropore openings, preventing excessively rapid growth and the resulting "sealing effect," thus achieving uniform and dense filling of the micropores from the inside out.
[0031] Furthermore, this invention also relates to a "resistivity gradient conductive structure," which is disposed on the side of an aluminum foil substrate away from the micropores to improve the electrical connection performance between the electrode foil and an external circuit. It is not a single conductive layer, but rather composed of at least two, typically three or more, conductive materials with gradient resistivity layered sequentially, such as a conductive carbon layer, an alloy transition layer, and a high-conductivity outer layer. This design aims to smoothly transition the conductivity difference between the internal semiconductor-like composite electrolyte and the external highly conductive metal electrode, thereby effectively reducing interfacial contact resistance.
[0032] In existing technologies, the electrode foil of multilayer aluminum electrolytic capacitors often suffers from uneven filling of conductive polymer due to the large aspect ratio of micropores during fabrication, resulting in a "sealing effect" that prevents deep channels from effectively participating in charge storage. Simultaneously, the significant difference in thermal expansion coefficients between the conductive polymer and the inorganic dielectric layer leads to poor device stability at high temperatures and a significant increase in equivalent series resistance (ESR). This invention addresses these problems by constructing an interpenetrating network structure for synergistic electron and ion transport within the micropores, combined with a gradient concentration impregnation strategy, a resistance gradient conductive structure, and other techniques. This systematically improves the capacitance extraction rate and high-temperature stability of the electrode foil while reducing its equivalent series resistance. The specific technical solution of this invention will be described in detail below.
[0033] Please see Figure 1 This illustrates the overall flow of an electrode foil preparation method in one embodiment of the present invention. The method first includes surface activation treatment (S110) of the inner walls of the micropores of an aluminum foil that has undergone etching and anodizing pretreatment (S100) to form a microporous structure with an alumina dielectric layer. The purpose of this step is to improve the hydrophilicity of the hydrophobic alumina dielectric layer surface, enhance its wetting ability with subsequent water-based reaction solutions, and create prerequisites for the uniform and deep filling of the conductive polymer.
[0034] Subsequently, in order to precisely control the formation area of the subsequent functional layers and avoid contamination of the electrode leads that could lead to leakage or short circuits, a polymerization area limitation (S200) is required. This step involves coating the reserved electrode lead area with an insulating shielding material to physically isolate the area, ensuring that subsequent polymerization reactions and gel filling occur only within the active area of the electrode.
[0035] Next, the core process proceeds to the multiple-cycle in-situ polymerization step (S300), which aims to construct three-dimensional continuous electron transport channels within the micropores. By alternately impregnating monomer and oxidant solutions, the conductive polymer grows layer by layer on the inner walls of the micropores. This invention preferably employs a gradient concentration impregnation strategy to overcome the "sealing effect" and achieve efficient and uniform filling of the micropores.
[0036] After the electron transport channels are constructed, a gel electrolyte composite step (S400) is performed. An aluminum foil with a conductive polymer network is immersed in a curable gel electrolyte, and in-situ curing is initiated by heating or light exposure. This forms a solid, ion-rich gel electrolyte within the gaps in the conductive polymer network framework, constituting the ion transport channels. At this point, the interpenetrating network structure within the micropores is formed.
[0037] To reduce the contact resistance between the electrode foil and the external circuit, a resistance gradient conductive structure needs to be prepared on the back side of the aluminum foil (S500). This step achieves a smooth transition in conductivity by sequentially depositing materials with different conductivity. Finally, the prepared electrode foil (anode foil), cathode foil, separator, etc., are assembled into a multilayer core, and then encapsulated and post-processed (S600) to obtain the finished multilayer aluminum electrolytic capacitor.
[0038] The following detailed explanation of each step in the above process is provided with reference to a specific embodiment. This embodiment provides a method for preparing electrode foil for multilayer aluminum electrolytic capacitors, the specific steps of which are as follows: First, the aluminum foil undergoes pretreatment. High-purity aluminum foil with a purity of 99.99% is selected as the substrate, and a high-density, high-aspect-ratio microporous tunnel structure is formed on its surface through conventional electrochemical etching processes. Subsequently, anodizing is performed to generate a uniformly thick and dense alumina dielectric layer 20 on the surface of the aluminum foil substrate 10 and the inner walls of the micropores. After pretreatment, the aluminum foil is thoroughly cleaned with deionized water and dried for later use.
[0039] After pretreatment, surface activation treatment was performed on the inner walls of the micropores. The aluminum foil with the alumina dielectric layer 20 was placed in an oxygen plasma environment with a radio frequency power of 200W and an oxygen flow rate of 50sccm for 5 minutes. The high-energy particles in the plasma bombarded the alumina surface, introducing a large number of active sites such as hydroxyl groups. This treatment significantly increased the surface energy of the alumina dielectric layer; in this embodiment, the surface energy increased from 45mN / m before treatment to 72mN / m, and the contact angle of water droplets on the surface decreased significantly from 68° to 22°. This indicates that the hydrophilicity of the dielectric layer surface was greatly improved, laying a solid foundation for the subsequent reaction solution to smoothly and deeply penetrate to the bottom of the micropores.
[0040] Next, the polymerization area is defined. A specific area for the electrode leads is pre-planned on the aluminum foil, and a double-layer shielding structure is precisely coated in this area using screen printing technology. The inner layer is an epoxy resin-based shielding adhesive with a coating thickness of 10 μm. After printing, it is heat-cured at 120°C for 30 minutes to form a dense, chemically resistant physical barrier layer. Subsequently, a 3 μm thick fluorocarbon resin-based hydrophobic shielding adhesive is coated on top of the cured inner layer as the outer layer, and cured by ultraviolet (UV) light irradiation. This outer layer has extremely low surface energy and exhibits excellent hydrophobicity. This double-layer shielding structure design, through the physical barrier of the inner layer and the surface energy repulsion of the outer layer, ensures that acidic or alkaline aqueous polymerization solutions will not corrode or adhere to the electrode leads during subsequent multiple impregnation processes, thereby greatly improving manufacturing precision and product yield.
[0041] Next, multiple cycles of in-situ polymerization were performed to generate a PEDOT conductive network 30 within the micropores, serving as an electron transport channel. In this embodiment, poly(3,4-ethylenedioxythiophene) (PEDOT) was selected as the conductive polymer, and the total number of polymerization cycles was set to 18. The polymerization process employed an alternating impregnation method; specifically, the monomer solution was an acetonitrile solution of 3,4-ethylenedioxythiophene (PEDOT), and the oxidant solution was an acetonitrile solution of ferric p-toluenesulfonate (Fe(III)-Tos).
[0042] To overcome the "sealing effect," this embodiment employs a gradient concentration impregnation strategy. Specific parameters are as follows: for the first five cycles, a higher concentration solution is used, with EDOT monomer at 0.10 M and Fe(III)-Tos oxidant at 0.08 M; for the middle six cycles (cycles 6 to 11), the concentration is appropriately reduced to 0.065 M for monomer and 0.055 M for oxidant; for the subsequent seven cycles (cycles 12 to 18), a lower concentration is used, with 0.04 M for monomer and 0.03 M for oxidant. This high-to-low concentration gradient design ensures that monomers can effectively penetrate deep into the pores during the initial reaction, while the lower concentration in the later stages allows for precise control of pore growth, preventing premature sealing.
[0043] To further enhance the conductivity of the conductive polymer network, sodium polystyrene sulfonate (PSS) at 10% of the total mass of the oxidant was added as a dopant when preparing the oxidant solution. The presence of the PSS macromolecular chains facilitates the formation of an ordered PEDOT:PSS complex, which increases the conductivity from approximately 10 S / cm to 100-300 S / cm, thereby significantly reducing the resistance of the electron transport channels.
[0044] During each impregnation process of the monomer and oxidant solutions, ultrasonic treatment at a frequency of 60 kHz for 2 minutes was applied. The cavitation effect generated by ultrasound in the liquid creates microjets and shock waves, effectively removing any tiny bubbles that may exist within the micropores and enhancing convection and diffusion of the liquid into the depths of the micropores, further aiding in the uniform penetration of the reactants. The specific operation for a single cycle was as follows: aluminum foil was vacuum impregnated in the EDOT monomer solution for 60 seconds, drained, and then vacuum impregnated in the oxidant solution for 70 seconds, followed by polymerization at a constant temperature of 70°C for 15 minutes. After 18 cycles, cross-sections were observed and analyzed using scanning electron microscopy (SEM). The results showed that the effective filling rate of the micropores (i.e., the percentage of polymer volume to the total micropore volume) reached 86%, significantly higher than the 62% achieved by the traditional fixed-concentration process.
[0045] After forming a dense electron transport channel, a gel electrolyte composite step is performed to construct an ion transport channel. First, a thermosetting gel electrolyte is prepared, the components of which, by mass percentage, are: polyethylene glycol diacrylate (PEGDA, molecular weight 700) 4.0%, N,N'-methylenebisacrylamide (as a crosslinking agent) 0.2%, azobisisobutyronitrile (AIBN, as a thermal initiator) 0.35%, ammonium adipate (as a conductive salt) 1.8%, and nano-silica (average particle size 30nm) 0.6%, with the balance being high-purity deionized water.
[0046] An aluminum foil with a PEDOT:PSS conductive polymer network was completely immersed in the prepared gel electrolyte and kept under a vacuum of at least -0.095 MPa for 30 minutes. This negative pressure environment helps the liquid electrolyte completely expel gas from the gaps and micropores of the PEDOT:PSS network, ensuring complete wetting. After impregnation, the aluminum foil was removed from the electrolyte and placed in an oven at 100°C for curing for 60 minutes. Under heating conditions, the thermal initiator AIBN decomposes to generate active free radicals, initiating a crosslinking polymerization reaction between the PEGDA monomer and the crosslinking agent, transforming the liquid electrolyte from a liquid state into a solid gel electrolyte 40 with a three-dimensional network structure.
[0047] like Figure 2 As shown, this in-situ curing process allows the formed gel electrolyte 40 to tightly fill all the voids in the pre-formed PEDOT conductive network 30. The two intertwine and permeate each other at the micron and even nanoscale, ultimately forming an ideal interpenetrating network structure within the micropores. In this structure, the PEDOT conductive network 30 constitutes a continuous electron transport channel, while the gel electrolyte 40 constitutes a continuous ion transport channel. Their synergistic effect provides the structural basis for the electrode foil to achieve high capacity extraction and low resistance.
[0048] Next, the resistivity gradient conductive structure was prepared. On the flat surface of the aluminum foil with the already formed interpenetrating network structure (i.e., the side facing away from the micropores), the resistivity gradient conductive structure was constructed through a multilayer coating and deposition process. First, a layer of conductive carbon paste was uniformly coated by a blade coating method to form a conductive carbon layer 50 with a thickness of 8 μm, and then dried at 60 °C for 40 minutes. This carbon layer has a resistivity of approximately 2 × 10⁻² Ω·cm and exhibits good physical compatibility and adhesion with the internal polymer / gel composite system, playing a preliminary role in reducing contact resistance and buffering stress.
[0049] Next, a 1 μm thick silver-palladium alloy layer 55 is deposited on the surface of the conductive carbon layer 50 using magnetron sputtering. In this embodiment, the target material is Ag-15%Pd alloy, and the sputtering process parameters are: vacuum background 5 × 10⁻⁻⁻⁶. 4 The sputtering parameters were: Pa, sputtering power 150 W, argon flow rate 30 sccm, and sputtering time 10 minutes. The resistivity of the alloy layer was approximately 8 × 10⁻⁻⁻⁶. 5 Ω·cm plays a crucial transitional role.
[0050] Finally, a highly conductive silver paste is uniformly coated onto the surface of the silver-palladium alloy layer 55 to form a conductive silver layer 60 with a thickness of 5 μm, and then cured at 80°C for 45 minutes. The resistivity of this conductive silver layer 60 is as low as approximately 1.8 × 10⁻⁻⁻⁻⁶. 6 Ω·cm provides an excellent conductive interface for external circuit connections. For example... Figure 3 As shown, by constructing a conductive carbon layer 50, a silver-palladium alloy layer 55, and a conductive silver layer 60, a resistivity ranging from 2 × 10⁻² Ω·cm to 8 × 10⁻ 5 From Ω·cm to 1.8×10⁻ 6 The gradient transition structure with an Ω·cm effectively buffers the significant conductivity difference between the internal semiconductor composite electrolyte and the external highly conductive metal electrode, thereby minimizing the interfacial contact resistance. Thus, a complete anode foil 70 with a multilayer functional structure is fabricated.
[0051] Finally, the capacitors are assembled and post-processed. Please refer to [link / reference]. Figure 4 Multiple anode foils 70 prepared by the above method, along with a corresponding number of cathode foils 80 and an insulating diaphragm 90 for electrical insulation, are alternately and precisely stacked in the order of anode-diaphragm-cathode-diaphragm to form a multi-layered stacked core. During the stacking process, the electrode lead-out regions of all anode foils 70 not covered by the functional layer are collected and soldered or pressed onto the positive electrode pin 100. Similarly, the electrode lead-out regions of all cathode foils 80 are collected and connected to the negative electrode pin 110.
[0052] The tightly pressed, multilayered core is inserted into a prefabricated encapsulation shell 120 and sealed using methods such as injection molding or epoxy resin potting to protect the internal structure from external environmental influences. After encapsulation, the capacitor is subjected to its rated voltage and aged at 105°C for 2 hours. This process helps repair minor defects that may have occurred during the cutting and stacking of the alumina dielectric layer 20, stabilizing the capacitor's electrical performance. After aging, key parameters such as capacitance, ESR, and leakage current are comprehensively tested to select qualified finished products.
[0053] As a variant implementation, the surface activation treatment of the microporous inner wall can also be carried out by chemical treatment. For example, in another embodiment, this step differs from the previous embodiment in that a silane coupling agent impregnation method is used instead of plasma treatment. Specifically, the aluminum foil with the dielectric layer is completely immersed in an ethanol solution of γ-glycidoxypropyltrimethoxysilane with a concentration of 1.0 wt% for 15 minutes. After removal, it is dried in an oven at 80°C for 40 minutes, allowing the silane coupling agent to hydrolyze and condense on the alumina surface, forming a stable organic active layer. After this treatment, the water droplet contact angle on the alumina surface is also significantly reduced from 68° to 35°, proving that it can also effectively improve the surface wettability, laying a good foundation for subsequent steps.
[0054] The specific parameters in the gradient concentration impregnation strategy can also be adjusted according to the actual micropore structure and process requirements. In another embodiment, the difference between this step and the previous embodiment is that the specific parameters of the gradient concentration impregnation strategy are adjusted as follows: for the first 5 cycles, the monomer concentration is 0.08M and the oxidant concentration is 0.06M; for the middle 7 cycles (cycles 6-12), the monomer concentration is 0.05M and the oxidant concentration is 0.04M; for the subsequent 6 cycles (cycles 13-18), the monomer concentration is 0.03M and the oxidant concentration is 0.02M. The total number of cycles is also 18. Using this set of parameters, the final measured effective micropore filling rate reached 84%, which also achieved the goal of high filling rate, indicating that the gradient concentration strategy of the present invention has a certain degree of process tolerance.
[0055] The formulation of the gel electrolyte can also be adjusted to optimize specific properties. For example, in another embodiment, the difference from the previous embodiment is that the amount of nano-silica added to the gel electrolyte is adjusted to 0.3 wt%, and the mass percentage of the remaining components is adjusted accordingly. The capacitor prepared using this formulation, after 1000 hours of accelerated aging testing at 125°C, showed an ESR change of 22% and a capacitance retention of 92%. This indicates that even with a reduced amount of nanofiller, excellent high-temperature stability can still be achieved, and also demonstrates that the addition of nano-silica plays a crucial role in improving thermal stability.
[0056] The formation method of the alloy transition layer in the preparation of the resistance gradient conductive structure is not unique. In another embodiment, the difference from the previous embodiment is that the silver-palladium alloy layer 55 is formed by chemical plating rather than magnetron sputtering. Specifically, the aluminum foil coated with a carbon layer is immersed in a chemical silver-palladium plating solution. The composition of the plating solution is: 5 g / L silver nitrate, 1.5 g / L palladium chloride, 40 g / L ethylenediaminetetraacetic acid, and 20 ml / L hydrazine hydrate. The pH of the plating solution is adjusted to 10, the temperature is controlled at 40°C, and the plating time is 15 minutes. This method forms a 1.2 μm thick Ag-80%Pd alloy layer on the carbon layer surface. This chemical plating method uses simple equipment, has low cost, and can still achieve the purpose of forming an alloy transition layer, providing more options for the industrial production of this invention.
[0057] The present invention also provides an electrode foil for a multilayer aluminum electrolytic capacitor, prepared by any of the methods described above. For example... Figure 3 As shown, the core structural feature of this electrode foil product is that a special interpenetrating network structure is provided inside the microporous aluminum foil substrate 10 with an alumina dielectric layer 20, and the inner walls of the micropores of the aluminum foil are surface activated. This interpenetrating network structure consists of two parts: one part is a three-dimensional continuous electron transport channel 30 composed of a PSS-doped conductive polymer, such as poly(3,4-ethylenedioxythiophene); the other part is an ion transport channel 40 filled in the gaps between these electron transport channels, composed of a polyethylene glycol-based gel electrolyte containing nanoscale inorganic fillers (such as nano-silica).
[0058] More specifically, such as Figure 2 The magnified view of the micropores shows that the PEDOT conductive network 30, like a skeleton, is attached to the surface of the alumina dielectric layer 20 and runs through the entire micropore, while the gel electrolyte 40 fills all the gaps in the skeleton like a sponge. This structure allows electrons and ions to find their own efficient and continuous transport paths at any location in the micropores, thus fundamentally solving the problem of unutilized deep capacitance caused by poor ion conduction in traditional solid-state electrolyte capacitors.
[0059] Furthermore, the electrode foil also has a resistance gradient conductive structure on the surface of the aluminum foil substrate 10 opposite to the micropores. For example... Figure 3As shown, the structure comprises a conductive carbon layer 50, a silver-palladium alloy layer 55, and a highly conductive outer layer (such as a conductive silver layer 60) stacked sequentially. This multilayer structure design allows for a smooth transition in resistance from the inside of the electrode foil to the outer pins, avoiding high interface resistance caused by abrupt changes in material conductivity, thereby significantly reducing the overall equivalent series resistance of the capacitor. Simultaneously, a double-layer shielding structure is coated in the predetermined electrode lead-out region of the electrode foil. This region does not form a conductive polymer network or gel electrolyte, ensuring the insulation and cleanliness of the lead-out terminals.
[0060] The present invention also provides a curable gel electrolyte composition specifically designed to form ion transport channels during the preparation of the electrode foil of the present invention. Its components, by mass percentage, preferably include: 3.0% to 5.0% of a crosslinkable monomer, such as polyethylene glycol diacrylate (PEGDA); 0.1% to 0.3% of a crosslinking agent, such as N,N'-methylenebisacrylamide; 0.2% to 0.5% of an initiator, such as the thermal initiator azobisisobutyronitrile (AIBN); 1.0% to 2.5% of a conductive salt, such as an ammonium organic carboxylate salt, such as ammonium adipate, for providing conductive ions; and 0.3% to 0.8% of a nanoscale inorganic filler, such as nano-silica. The balance is a solvent, typically deionized water.
[0061] In this composition, crosslinkable monomers and crosslinking agents can undergo in-situ polymerization and crosslinking under the action of an initiator through heating or light irradiation, forming a solid gel framework with a three-dimensional network structure. The conductive salt, dissolved in the solvent and bound within the gel network, constitutes the main source of ionic conductivity. The introduction of nanoscale inorganic fillers serves two purposes: firstly, as physical crosslinking points, enhancing the mechanical strength and toughness of the gel; secondly, their inorganic properties effectively suppress polymer chain movement at high temperatures, buffering the thermal expansion mismatch between the organic gel and the inorganic dielectric layer, thereby significantly improving the high-temperature stability and lifespan of the entire electrode foil and even the capacitor. This composition itself has independent practicality and can be applied to various electrochemical devices requiring in-situ formation of solid electrolytes.
[0062] The present invention also provides a multilayer aluminum electrolytic capacitor, characterized in that it uses the electrode foil described in any of the foregoing claims as its anode. For example... Figure 4As shown, the core of this capacitor is a laminated core composed of alternating stacks of multiple anode foils 70, cathode foils 80, and insulating diaphragms 90. Due to the special structure of the anode foils 70 as described in this invention, the entire capacitor exhibits excellent performance. For example, its equivalent series resistance at 100 kHz can be as low as below 5.0 mΩ, and its capacitance extraction rate at 120 Hz can be as high as over 92%. More importantly, it has excellent high-temperature stability; after aging at 150°C for 600 hours, the change rate of its equivalent series resistance does not exceed 100% of the initial value, and the capacitance decay rate is also extremely low.
[0063] To comprehensively verify the technical effects of the present invention, the following embodiments and comparative examples were set up. The process parameters for Example 1 were: surface activation method was plasma treatment (5 min), using a gradient concentration strategy of 18 cycles, PSS doping amount was 10 wt%, nano-SiO2 addition amount was 0.6 wt%, and the conductive layer structure was a carbon layer + magnetron sputtered Ag-Pd alloy layer + silver layer. Example 2 differed from Example 1 in that the surface activation method was silane coupling agent impregnation. Example 3 differed from Example 1 in that the specific concentration value of the gradient concentration strategy was adjusted. Example 4 differed from Example 1 in that the nano-SiO2 addition amount was 0.3 wt%. Example 5 differed from Example 1 in that the Ag-Pd alloy layer in the conductive layer structure was formed by chemical plating. Comparative Example 1 differed from Example 1 in that surface activation treatment was omitted, a fixed concentration impregnation was used, and no PSS dopant was added. Its verification purpose was to verify the effect of the "surface activation + gradient concentration + PSS doping" combination on improving micropore filling and capacity. The difference between Comparative Example 2 and Example 1 is that the gel electrolyte composite step is omitted. Its purpose is to verify the contribution of the ion pathway in the "electron-ion dual transport channel" to capacity extraction and high-temperature stability. The difference between Comparative Example 3 and Example 1 is that the composite conductive layer only contains a carbon layer and a silver layer, without forming an intermediate alloy transition layer. Its purpose is to verify the effect of the "carbon layer + alloy layer + silver layer" three-layer resistance gradient structure on reducing ESR.
[0064] The performance of the capacitors prepared in the above embodiments and comparative examples was tested, and the following results were obtained.
[0065] Table 1 Comparison of process parameters between the examples and comparative examples
[0066] 2. Performance test results of the examples and comparative examples
[0067] Comparing the results of Example 1 and Comparative Example 2, it can be found that Comparative Example 2, lacking the gel electrolyte as an ion transport channel, has a capacity extraction rate of only 80%, far lower than the 94% of Example 1. More importantly, after aging at 150°C for 600 hours, its ESR change rate is as high as +640%, and its capacity decay reaches 35%, indicating severe performance degradation. In contrast, Example 1, under the same aging conditions, has an ESR change rate of only +85% and a capacity decay of only 8%. This fully demonstrates that the interpenetrating network structure composed of electron transport channels and ion transport channels constructed in this invention is the core and key to achieving high capacity extraction and excellent high-temperature stability. A single electron channel cannot effectively solve the problem of deep ion migration, nor can it maintain structural stability at high temperatures.
[0068] Comparing the results of Example 1 and Comparative Example 3, Comparative Example 3, lacking an alloy transition layer, had an ESR of 6.8 mΩ, while Example 1, by introducing a silver-palladium alloy layer to construct a three-level resistance gradient structure, further reduced its ESR to 4.6 mΩ, a reduction of 32%. This clearly demonstrates that the design of a resistance gradient conductive structure, especially the introduction of an alloy transition layer, has a significant effect on reducing interfacial contact resistance and optimizing charge discharge paths.
[0069] Based on the test data from Examples 1 to 5, it can be seen that the beneficial effects of this invention can be achieved regardless of whether plasma treatment or silane coupling agent treatment is used for surface activation, and whether magnetron sputtering or chemical plating is used to form the alloy layer. This demonstrates that the technical solution of this invention has good universality and process flexibility. The influence of parameter adjustment of the gradient concentration strategy and variation in the amount of nanofiller on the final performance is within a controllable range, which also proves the tolerance of the process.
[0070] In summary, this invention systematically solves several technical problems existing in the prior art, such as uneven micropore filling, poor ion conduction, poor high-temperature stability, and high interfacial contact resistance, through a series of innovative technical means, including surface activation treatment, double-layer shielding structure, gradient concentration impregnation strategy, PSS doping, construction of electron-ion interpenetrating network structure, nanofiller-reinforced gel electrolyte, and three-level resistance gradient conductive layer. The final electrode foil and its capacitor have achieved significant progress in key performance indicators such as capacitance extraction rate, equivalent series resistance, and high-temperature reliability.
[0071] The above description is merely a preferred embodiment of the present invention and is not intended to limit the invention. Various modifications and variations can be made to the present invention by those skilled in the art. Any modifications, equivalent substitutions, improvements, etc., made within the spirit and principles of the present invention should be included within the scope of protection of the present invention.
Claims
1. A method for preparing an electrode foil for a multilayer aluminum electrolytic capacitor, the electrode foil comprising an aluminum foil with micropores, characterized in that, include: The inner walls of the micropores are pretreated to improve their wettability to the subsequent reaction solution. An interpenetrating network structure containing electron transport channels and ion transport channels is formed within the micropores.
2. The method according to claim 1, characterized in that, The steps for forming the interpenetrating network structure include: A gradient concentration impregnation strategy is employed for multiple cycles of in-situ polymerization to generate a conductive polymer network within the micropores, serving as the electron transport channel. The initial cycles utilize higher concentrations of monomer and oxidant solutions, while the subsequent cycles employ lower concentrations. An aluminum foil with a conductive polymer network is immersed in a curable gel electrolyte containing nanoscale inorganic fillers, and the gel electrolyte is cured in situ to form a gel electrolyte that serves as an ion transport channel in the gaps of the conductive polymer network.
3. The method according to claim 2, characterized in that, During the multiple cycles of in-situ polymerization, ultrasonic-assisted treatment is applied, and sodium polystyrene sulfonate is added to the oxidant solution as a dopant.
4. The method according to claim 1, characterized in that: The pretreatment includes plasma treatment of the aluminum foil or chemical treatment with a silane coupling agent solution; The method further includes coating the untreated areas of the aluminum foil with a double-layer shielding structure comprising a chemically resistant inner layer and a hydrophobic outer layer; and The method further includes sequentially depositing a conductive transition layer, an alloy transition layer, and a high-conductivity outer layer on one side surface of the aluminum foil substrate to form a resistance gradient conductive structure.
5. An electrode foil for a multilayer aluminum electrolytic capacitor, comprising an aluminum foil having micropores, characterized in that, An interpenetrating network structure is disposed within the micropores, the interpenetrating network structure comprising: Electron transport channels made of conductive polymers; and Ion transport channels composed of gel electrolytes fill the gaps in the electron transport channels.
6. The electrode foil according to claim 5, characterized in that, The gel electrolyte contains nano-silica as an additive to improve mechanical properties and thermal stability.
7. The electrode foil according to claim 5, characterized in that, The electrode foil also includes a resistance gradient conductive structure disposed on one side surface of the aluminum foil substrate. The resistance gradient conductive structure includes a conductive carbon layer, a silver-palladium alloy layer and a highly conductive outer layer stacked sequentially.
8. A curable gel electrolyte, characterized in that, Its components include: crosslinkable monomers, crosslinking agents, initiators, conductive salts, and nanoscale inorganic fillers for improving the mechanical properties and thermal stability after curing.
9. The curable gel electrolyte according to claim 8, characterized in that, The crosslinkable monomer is polyethylene glycol diacrylate, and the conductive salt is an organic carboxylic acid ammonium salt.
10. A multilayer aluminum electrolytic capacitor, characterized in that, Includes the electrode foil according to any one of claims 5, 6 or 7.
